Pharmacokinetic optimitzation of CCG-203971: Novel inhibitors of the Rho/MRTF/SRF transcriptional pathway as potential antifibrotic therapeutics for systemic scleroderma. Issue 8 (15th April 2017) - Hutchings, Kim M.; Lisabeth, Erika M.; Rajeswaran, Walajapet; Wilson, Michael W.; Sorenson, Roderick J.; Campbell, Phillip L.; Ruth, Jeffrey H.; Amin, Asif; Tsou, Pei-Suen; Leipprandt, Jeffrey R.; Olson, Samuel R.; Wen, Bo; et al.
Graphical abstract: Abstract: We recently reported the development of a novel inhibitor of Rho-mediated gene transcription (1, CCG-203971) that is efficacious in multiple animal models of acute fibrosis, including scleroderma, when given intraperitoneally. The modest in vivo potency and poor pharmacokinetics (PK) of this lead, however, make it unsuitable for long term efficacy studies. We therefore undertook a systematic medicinal chemistry effort to improve both the metabolic stability and the solubility of1, resulting in the identification of two analogs achieving over 10-fold increases in plasma exposures in mice. We subsequently showed that one of these analogs (8f, CCG-232601) could inhibit the development of bleomycin-induced dermal fibrosis in mice when administered orally at 50 mg/kg, an effect that was comparable to what we had observed earlier with1 at a 4-fold higher IP dose.